Kyrgyz Republic Country Program Evaluation : Approach Paper - Independent Evaluation Group (Washington, DC : World Bank, 2022)
The Country Program Evaluation (CPE) for the Kyrgyz Republic seeks to assess the World Bank Group’s efforts to help the Kyrgyz Republic address its main development challenges. The evaluation will cover fiscal years (FY)14–21 and is timed to inform the next Country Partnership Framework (CPF) between the Kyrgyz Republic and the Bank Group. The evaluation will assess (i) how relevant was the Bank Group’s strategy and how it evolved over time, given changes in the country context and lessons from experience; (ii) the extent to which Bank Group support helped the Kyrgyz Republic foster increased private sector–led growth to reduce economic vulnerability; (iii) the extent to which Bank Group support helped improve central government governance and institutional capacity; and (vi) the extent to which Bank Group support improved local governance and the quality of, and access to, local public services.